The Klingon batbugs: Morphological adaptations in the primitive bat bugs, Bucimex chilensis and Primicimex cavernis, including updated phylogeny of Cimicidae - Ossa G.; Johnson J.S.; Puisto A.I.E.; Rinne V.; Sääksjärvi I.E.; Waag A.; Vesterinen E.J.; Lilley T.M. (WILEY, 2022)
The Cimicidae is a family of blood-dependent ectoparasites in which dispersion capacity is greatly associated with host movements. Bats are the ancestral and most prevalent hosts for cimicids. Cimicids have a worldwide distribution matching that of their hosts, but the global classification is incomplete, especially for species outside the most common Cimicidae taxa. In this study, we place a little-studied cimicid species, Bucimex chilensis, within a comprehensive molecular phylogeny of Cimicidae by sequencing the genomic regions of this and other closely related species. For this study, we collected B.chilensis females from Myotis chiloensis in Tierra del Fuego, 1,300km further south than previously known southernmost distribution boundary. We also sequenced COI regions from Primicimex cavernis, a species which together with B. chilensis comprise the entire subfamily Primiciminae. Using Bayesian posterior probability and maximum-likelihood approaches, we found that B.chilensis and P.cavernis clustered close to each other in the molecular analyses, receiving support from similar morphological features, agreeing with the morphology-based taxonomic placement of the two species within the subfamily Primiciminae. We also describe a previously unrecognized morphological adaptation of the tarsal structure, which allows the austral bat ectoparasite, B.chilensis, to cling on to the pelage of its known host, the Chilean myotis (Myotis chiloensis). Through a morphological study and behavioral observation, we elucidate how this tarsal structure operates, and we hypothesize that by clinging in the host pelage, B.chilensis is able to disperse effectively to new areas despite low host density. This is a unique feature shared by P.cavernis, the only other species in Primiciminae.